Mixing in the upper western equatorial Pacific driven by westerly wind event - Shen, Duhan; Wang, Jianing; Liu, Zhiyu; Wang, Fan (Frontiers in Marine Science, 2023)
Diapycnal mixing in the upper western equatorial Pacific (WEP) plays an important role in the tropical air–sea interactions and in the formation of the global climate system. Yet, the WEP is uniquely rich in water masses originating from the two hemispheres and in multiscale processes of different dynamical nature, thus creating a complex regime of mixing remains to be fully characterized by elaborate observations. Here, on the basis of microstructure measurements in the WEP, we report the observations on a strong deep cycle turbulence extending well into the upper thermocline by westerly wind event, with the turbulent kinetic energy dissipation rate ε O(10−8–10−7) W kg−1 and diapycnal diffusivity Kρ∼O(10−4) m2 s−1. Below the deep cycle turbulence layer, turbulence and mixing are generally weak with ε O(10−10–10−9) W kg−1 and Kρ∼O(10−7–10−6) m2 s−1, a prototype of the weak mixing nature of the low-latitude western Pacific. The observed turbulence below the deep cycle turbulence layer can be satisfactorily scaled by either the MacKinnon–Gregg model or the Richardson number–based model with tuned model parameters.